Responsible finance: application and challenges for society, governments and corporations - V. I. Pyatanova; I. A. Pyatanov (Управление)
The topic of Responsible Finance is becoming an important issue in the functioning of our financial systems. There are many interesting developments in social, governmental and corporate perspectives that promote more ethical and sustainable principles of making financial decisions, allocating resources and capital. The boom in ESG investing (taking into account Environmental, Social and Governance factors) over the last 10 years suggests the great importance of this topic for funding allocation worldwide. Investment proj ects are now assessed on a variety of metrics, not only based on their potential financial gains. Governments also have a role to play, as they support private initiatives and reconsider a huge variety of their projects to account for these additional factors that eventually impact population’s welfare. All economic agents should pay attention to this transformation to not miss out on the new standards of financial responsibility. These changes present great opportunities for the world of finance, whilst having few drawbacks. In this article a closer look at the founding principles of financial responsibility is taken. Authors examine how these principles shape the financial policy with concrete examples from social, corporate and government perspectives. Authors also emphasize the factors that potentially limit the unitary acceptance of such practices around the world.